Implementasi KKN AKSARA UMKLA: Pemberdayaan Masyarakat melalui Digitalisasi UMKM, Kesehatan, dan Sosial di Dukuh Marangan - Febriyan Ichlasul Imam; Safinatusyifa Amini; Sri Rejeki; Marlina Azzahra; Fauzie Rahman; Fawati Titi Suyana; Fika Nurhidayah; Fitri Azzizatul Ni'mah; Deswandya Azzahra; Muhammad Naufal Nur Hakim; Mia Wiritaniya; Sovi Reviana Putri; Erma Widyastuti (Universitas Muhammadiyah Klaten, 2026)
Real Work Lecture (KKN) is a form of community service that must be carried out by all students of the University of Muhammadiyah Klaten (UMKLA). Group 04 KKN UMKLA AKSARA 2025 has been held in Marangan Village, Jimbung, Kalikotes, Klaten, Central Java, from July 31, 2025 to August 30, 2025. This activity aims to apply the knowledge that has been learned from campus while helping to solve problems in the surrounding community, especially Marangan Village. Field work program created in several areas, such as education (Dauroh or Intensive Religious Study), economy (digitization of MSMEs), Health (Posyandu counseling), and Social Community (assisting activities at the TPA). With an approach that directly involves the society the students strive to increase society awareness, provide motivation, and assist in the implementation of these programs. The results of this Field Work demonstrated increased resident's participation, enthusiasm for MSME digitalization, outreach at integrated health in Posyandu, and bring up of new ideas for local resource management. This Field Work program successfully fostered strong collaboration between students, village officials, and residents, resulting in sustainable positive change.